2021
DOI: 10.1177/0958305x211030112
|View full text |Cite
|
Sign up to set email alerts
|

Optimum sizing and simulation of hybrid renewable energy system for remote area

Abstract: In current scenario, people tend to move towards outskirts and like to settle in places that are close to nature. But, due to urban lifestyle and to fulfill the basic needs, demand of electricity remains the same as in urban areas. This demand of electricity can be only fulfilled by using hybrid renewable energy resources, which is easily available in outskirts. Renewable energy resources are unreliable and more expensive. Researchers are working to make, it more reliable and economic in terms of utilization. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…It was observed that the proposed approach is a viable option to be applied for the optimal design of a hybrid generation system. Investigating the optimal design of a HES that consists of PV, wind, and battery using a metaheuristic grasshopper optimization algorithm to provide electricity for remote areas was proposed in [15]. The results show that the proposed algorithm is efficient in finding the optimal design of the suggested HES.…”
Section: Introductionmentioning
confidence: 99%
“…It was observed that the proposed approach is a viable option to be applied for the optimal design of a hybrid generation system. Investigating the optimal design of a HES that consists of PV, wind, and battery using a metaheuristic grasshopper optimization algorithm to provide electricity for remote areas was proposed in [15]. The results show that the proposed algorithm is efficient in finding the optimal design of the suggested HES.…”
Section: Introductionmentioning
confidence: 99%
“…It was determined that the suggested strategy is an effective option to use for the optimum design of a half-and-half age framework. To provide energy to remote areas, it was suggested to investigate the best configuration of a HES made up of solar, wind, and batteries using a metaheuristic grasshopper improvement computation [14]. In [15], An energy channel calculation was used to determine the best measurement technique for a PV, wind turbine, and battery crossover age architecture.…”
Section: Introductionmentioning
confidence: 99%
“…For the best design of a hybrid framework, it was concluded that the proposed approach is an efficient option. Using a metaheuristic grasshopper improvement computation, it was suggested that the best configuration of a HES composed of solar, wind, and batteries be investigated in order to supply energy to remote areas [23].The best method for measuring a PV, wind turbine, and battery edge design was determined using an energy channel calculation in [24].The designers discovered that, furthermore to meeting the essential limitations, utilizing the energy network estimation in conjunction with the recommended method is helpful for establishing the ideal economic plan for the HES.…”
Section: Introductionmentioning
confidence: 99%